2025.6.101 - Cameron, John E. (Northwest Missouri State University, 2026)
Glass-plate negative photograph of two girls sitting in front of a cornfield, each is holding two small birds. A third child's legs and feet are visible on the left side of the photograph. Roughly 1/4 of the photograph is damaged.